PENTINGNYA PENDEKATAN HISTORIS DALAM MEMAHAMI SANAD HADIS NABI MUHAMMAD SAW - Sukron (Journal Khafi : Journal Of Islamic Studies, 2023)
In the early Islamic tradition, Sanad hadith has been used since ancient times and is a scientific tradition and system of transmission that can be maintained and accounted for. The elements of sanad in the narration of hadith are a very important part both in determining the quality of the hadith and in terms of quantity. The method used in this scientific work is theoretical analysis. In historical review, sanad is used by the Jewish religion or is found in the Jewish book, the Mishnah, including the Jahiliyah community in telling their silsila and poetry also uses the sanad method although it is not clear to what extent this method is needed. Hadith scholars Sanad hadith is part of religion.